Growth marketing concept : case study on Finnish companies - Orzheshkovskaya, Daria (2019)
The discipline of marketing has progressed from simple product selling into comprehensive approach of building long-term relationship with customers. Companies eligible for sustainable growth have shifted from product-oriented into customer focused business model. Because of the era of digitalization, consumers have unlimited power of choosing, thus customer relationship management has never been more difficult than now. Even though, role of marketing in overall company’s performance has been researched, there is gap in understanding, how exactly a company can grow by implementing marketing into a strategy. The concept of growth marketing, has received practical attention, but academic definition is missing. For that reason, this study attempts to find out, what does growth marketing mean and how it is implemented. Also, this research tries to clarify the tools and measurements applicable in the process of growth marketing. Because the phenomenon is new, abductive logic of qualitative case study has been performed. Existing scientific literature has been supported by empirical findings in order to see how marketing can help companies growing, and what is its input strength based on the type of growth chosen. Four interviews with expert agencies and five case companies were examined in consideration of their marketing activities. Hence, one expert company is the developer of growth marketing balanced scorecard and one case company has already implemented this concept into own operations. It is revealed that the composition of applicable tools and investments in each component of growth marketing concept depends on company’s strategic goal. Nevertheless, growth marketing is seen as a human-centric approach used by companies seeking for growth, where the highest potential is reached by balanced managerial strategic formation, effective management of relationship with employees for outstanding cooperation with customers.